Scriptural Interpretation at the Interface between Education and Religion, In Memory of Hans Conzelmann. - Florian Wilk (Editor) (Themes in Biblical Narrative, 2019)
Scriptural Interpretation at the Interface between Education and Religion examines prominent texts from Jewish, Christian, and Islamic communities with a view to determining to what extent education ( Bildung ) represents the precondition, the central feature and/or the aim of the interpretation of 'Holy Scripture' in antiquity. In particular, consideration is given to the exegetical techniques, the hermeneutical convictions and the contexts of intercultural exchange which determine the process of interpretation. The volume contains a methodological reflection as well as investigations of scriptural interpretation in Jewish texts from the 2nd and 1st centuries B.C.E., in New Testament writings, and in witnesses from late ancient Christianity and in the Qur'an. Finally, it contains a critical appraisal of the scholarly oeuvre of Hans Conzelmann. This work thus fosters scholarly understanding of the function of scriptural interpretation at the interface between education and religion.